Emergency Response Training Program for Theme Parks: Experiences of Taiwan. Issue Volume 34:Issue s1(2019) (May 2019) - Hsiau, Yawen; Liu, Yu-Han; Lin, Chi-Chun
Abstract : Introduction: "Tailor-made" training programs have been started in two theme parks in North and East Taiwan after the dust explosion of Ba-xien theme park in 2015. The training programs emphasized several areas. They work to strengthen the incident command system (ICS) and the skills of first responders, especially evacuation, placement, triage, and first aid, as well as to assist the park's cooperation with local disaster response units, such as the fire department and Health Bureau. Methods: The first step was to find out the practical problems of the two theme parks, and then make a one-year, tailor-made training program according to the needs of parks and different levels of staff: senior supervisors, middle-level district supervisors, and frontline colleagues. After the phased training, the training results are inspected in the non-scripted exercise mode. Results: It was found that the staff are relatively familiar with the evacuation process and placement of tourists. The initial emergency responses such as triage, first aid skills, and patient transport gradually improve after several drills. The ICS operation and communication also became more effective and efficient. The regional emergency response units could understand these theme parks capability and how to cooperate with them. Discussion: The experience of emergency response training and exercise in these two theme parks has shown that such a model is feasible and should be valued.